Effects of acidification on the survival of pathogens in reconstituted infant formula - Nemakonde, Mufunwa (University of the Witwatersrand, Johannesburg, 2023)
Infants are at a high risk of developing food-borne illnesses due to the consumption of powdered infant formulas (PIFs) contaminated by pathogenic microorganisms. These pathogens may be introduced during PIF production, transportation or during preparation and storage due to poor hygiene practices. Therefore, it is important to improve the microbiological safety of PIFs to reduce illness. Manufacturers have added further measures to ensure continued control of pathogenic microorganisms during the reconstitution and consumption, including the addition of prebiotics and probiotics, as well as acidification of the PIFs, which negatively affect the growth of pathogens. Different organic acids have been biologically or chemically added to commercial PIFs, however, little is known about the efficacy of the different acids in controlling pathogen growth post-reconstitution. The present study aimed to evaluate and compare the effects of two acids, namely citrate and lactate, integrated in commercial PIFs from two manufacturers on pathogen growth within the products. In Chapter 1, we present a review of the current literature pertaining to PIF production and consumption, its microbiological safety and key problem pathogens, as well as measures to control these pathogens (with specific emphasis on PIF acidification). In Chapter 2, the methodology of the present study is discussed. The effects of lactate and citrate incorporated in commercial PIFs against eight key PIF pathogens was evaluated using plate-based assays. Furthermore, the efficacy of PIF acidification at different storage temperatures and over prolonged storage periods was determined. Finally, to validate the effect of acidity on controlling pathogen growth, a spectrophotometric approach was used. Chapter 3 presents and discusses the key findings of the study. PIF acidification was found to negatively affect the growth of pathogens in comparison to the non-acidified infant formula. Acidification and storage at suboptimal temperatures resulted in little to no microbial growth. Lactate acidification of PIFs demonstrated greater inhibitory effects against most pathogens compared to citrate acidification. Further, lactate was found to have a bactericidal effect on the growth of some pathogens. Similarly, Luria Broth acidification resulted in the reduction of microbial growth. This validated that the acids and not other constituents of the infant formula were responsible for the inhibitory effect. Finally, Chapter 4 provides a summary of the key findings as well as recommendations and guidance on future studies which could be undertaken to enhance the effective control of pathogens in powdered infant formulas, thereby ensuring a safe and nutritious food source for infants.
A dissertation submitted in fulfilment of the requirements for the degree Master of Science to the Faculty of Science, in the School of Molecular and Cell Biology, at the University of the Witwatersrand, Johannesburg, 2023.
Keywords: Food-borne illnesses; Powdered infant formulas (PIFs); Lactate; Citrate; Non-acidified infant formula; Infants; UCTD; SDG-3: Good health and well-being